Retraction of ‘Analytical method development and validation of prasugrel in bulk and its pharmaceutical formulation using HPLC' (J App Pharm Sci, 2011; 01 (07): 172-175) (Journal of Applied Pharmaceutical Science)
This is to inform the readers that article titled ‘Analytical method development and validation of prasugrel in bulk and its pharmaceutical formulation using HPLX’ by G. Usha Rani, B. Chandrasekhar and N. Devanna has been retracted. It has come to the notice of editors of Journal of Applied Pharmaceutical Science that, this article contains lots of similarities to the article ‘Development and validation of HPLC method for determination of prasugrel in bulk and its pharmaceutical formulation’ by Ishaq et al., (2011). Thus, we retract this article from the literature according to the guidelines of Committee on Publication Ethics (Wager et al., 2009).